2019
DOI: 10.1053/j.gastro.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Demethylase KDM3A, Increased in Human Pancreatic Tumors, Regulates Expression of DCLK1 and Promotes Tumorigenesis in Mice

Abstract: BACKGROUND & AIMS: The histone lysine demethylase 3A (KDM3A) demethylates H3K9me1 and H3K9Me2 to increase gene transcription and is upregulated in tumors, including pancreatic tumors. We investigated its activities in pancreatic cancer cell lines and its regulation of the gene encoding doublecortin calmodulin-like kinase 1 (DCLK1), a marker of cancer stem cells. METHODS: We knocked down KDM3A in MiaPaCa-2 and S2-007 pancreatic cancer cell lines and overexpressed KDM3A in HPNE cells (human noncancerous pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 57 publications
1
42
1
Order By: Relevance
“…H3K9 dimethylation status can be demethylated by a histone demethylase KDM3A/JHDM2A/JMJD1A (46). A recent study showed that KDM3A knockdown suppresses DCLK1 expression in human pancreatic cancer cell (47). While our data contradicted these previous findings, there was a clear difference in the model used in the two studies.…”
Section: Discussioncontrasting
confidence: 97%
“…H3K9 dimethylation status can be demethylated by a histone demethylase KDM3A/JHDM2A/JMJD1A (46). A recent study showed that KDM3A knockdown suppresses DCLK1 expression in human pancreatic cancer cell (47). While our data contradicted these previous findings, there was a clear difference in the model used in the two studies.…”
Section: Discussioncontrasting
confidence: 97%
“…[17][18][19] Methylation of histone lysine is crucial for epigenetic correlated gene expression profiles in cancer. 20 In this study, we validated an interaction network involving KDM3A/ETS1/KIF14, in which KDM3A governs ETS1-mediated KIF14 transcription to promote CC growth in either cell and animal models with the further involvement of the Hedgehog signaling pathway.…”
Section: Discussionmentioning
confidence: 81%
“…[21][22][23] Here, the initial finding of the current study was that KDM3A was highly expressed in the collected tumor tissues from CC patients, and it led to a dismal 5-year survival rate, increased lymphatic metastasis, and decreased tumor differentiation rate in patients. Similarly, abundant expression of KDM3A has been noted as an independent unfavorable factor in patients with pancreatic tumor 20 and colorectal cancer 24 and epithelial ovarian cancer. 25 A high-expression profile of KDM3A was also found in CC cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…KDM3A , which belongs to the Lysine demethylases family, has been shown to play a role in carcinogenesis in multiple cancers and to be an optimal pharmacological target for pancreatic cancer (Lomberk, Iovanna, & Urrutia, 2016). A recent mice study showed knockdown of KDM3A in pancreatic cancer cell line reduced the invasive and sphere‐forming activities in culture and formation of orthotopic tumors (Dandawate et al, 2019). TRIP10 , whose overexpression may enhance pancreatic cancer cell migration, could be involved in the carcinogenesis of pancreatic cancer (Roignot et al, 2010).…”
Section: Discussionmentioning
confidence: 99%